Respostas

2013-05-28T22:15:00-03:00

2x+y=6-------------------->y=6-2x (vou substituir o y na equação de baixo por 6-2x)

2x+3y=2------------------>2x+3(6-2x)=2 (então é só resolver)

 

2x+3(6-2x)=2

2x+18-6x-2=0

-4x+16=0

-4x=-16           (-1)

4x=16

x=16/4

x=4

2013-05-28T23:02:21-03:00

2x+Y=6 . (-3)             2.4+Y=6                       |2X+Y=6  .  (-1)

-6x-3/y= -18               2.4+3Y=2                    | -2/X-Y=-6 

2x+3/y=2                    8+Y=6                         | 2/X+3Y=2

-4x=-16 . (-1)              8+3Y=2                       |2Y=-4

4X=16                         Y=6-8 Y=-2                 |Y=-4:2

X=16:4                         3Y=2-8                     | Y=-2

X=4                              3Y=-6                        | 

                                    Y=-6:3                       |

                                    Y=-2                          |

                                                                      |